The People's Jesus : trajectories in early Christianity - Scroggs, Robin; Johnson, Marshall D. (Minneapolis : Fortress Press, 2011)
"Seeking the patterns of thought that shaped early beliefs about Jesus as the Christ, the late Robin Scroggs explores the social settings that sparked the primary christological themes and traces their trajectories through the literature that made up the New Testament" -- Publisher's description.
Includes bibliographical references and index.
Keywords: Jesus Christ -- History of doctrines -- Early church, ca. 30-600.; Bible. -- Theology; Bible. -- Social scientific criticism